Acne in schoolchildren: no longer a concern for dermatologists. Issue 6682 (6th May 1989) - Rademaker, M.; Garioch, J. J.; Simpson, N. B.
Abstract : OBJECTIVE–To determine the prevalence and severity of acne among schoolchildren in Glasgow. DESIGN–Secondary schools in Glasgow were divided by postcode into five socioeconomic cluster groups. Different numbers of schools were selected at random from the five groups to ensure proportional representation. One class from each registration year of the chosen schools was selected at random and the whole class recruited into the study. SETTING–15 Secondary schools in Glasgow. SUBJECTS–2014 Randomly selected schoolchildren aged 12-17 (5% of total secondary school roll). INTERVENTIONS–None. END POINT–Assessment of facial acne by two independent examiners by a recognised acne scoring system. MEASUREMENTS AND MAIN RESULTS–The prevalence of acne in boys increased from 40% (75/189) at age 12 to 95% (108/114) at age 16, and in girls it increased from 61% (114/187) at age 12 to 83% (136/164) at age 16. On a scale of 0 to 10 only 18 boys (1.8%) and three girls (0.3%) had grades of acne of 1.0 or greater; most of the pupils had grade 0.05-0.375 (minimal) acne. Nine per cent of boys (88/973) and 14% of girls (145/1041) had visited their general practitioner specifically for advice on and treatment for acne; only five pupils (0.3%) had been referred to a dermatologist. CONCLUSIONS–Both the prevalence and severity of acne have decreased over the past 20 years. This has probably been due to improvement of treatment for acne by primary care doctors and the greater availability and use of over the counter preparations for acne.